Awal Mula Ide Pilihan Hukum: Sebuah Narasi Sampai Abad Ke-19 (The Genesis of Choice of Law: A Narrative up to the 19th Century) - Penasthika, Priskila Pratita (UI Scholars Hub, 2019)
The historical background of contractual choice of law is still hardly discussed in the literature of Indonesian private international law. The available literature merely focuses on the scope and limitation of the choice of law. The choice of law is accepted and discussed as a widely acknowledged doctrine without sufficiently addressing its origin and evolvement until it became the concept as we understand to date. Employing an exposition through the academic literature, this article studies the narrative that began the idea of contractual choice of law up to the end of the 19th century as an intricate idea in private international law.